Increased frequency of linezolid resistance among clinical Enterococcus faecium isolates from German hospital patients. Issue 2 (June 2015) - Klare, Ingo; Fleige, Carola; Geringer, Uta; Thürmer, Alexander; Bender, Jennifer; Mutters, Nico T.; Mischnik, Alexander; Werner, Guido
Highlights: We report an increasing prevalence of linezolid resistance among 4461 clinical Enterococcus faecium strains. >90% of linezolid-resistant isolates (232/251) contained the G2576T 23S rDNA mutation. We observed outbreaks with linezolid-resistant, vancomycin-resistant enterococci. In vitro growth experiments revealed stable linezolid resistance. Five linezolid-resistant isolates were cfr -positive. Abstract: Linezolid is an antibiotic of last resort for the treatment of infections with vancomycin-resistant enterococci (VRE). Here we report the increasing prevalence of linezolid resistance among clinical Enterococcus faecium strains from German hospital patients. Linezolid minimum inhibitory concentrations (MICs) were determined for 4461 clinical E. faecium strains isolated between 2008 and 2014. Isolates originated from the network of diagnostic laboratories collaborating with the National Reference Centre (NRC) for Staphylococci and Enterococci covering all German federal states. All linezolid-resistant isolates were determined by broth microdilution and confirmed by Etest as well as by analysing the 23S rDNA for putative mutations. Marker genes were determined by PCR. Genotyping was performed by Sma I macrorestriction analysis in pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) for selected isolates. An increase in linezolid resistance was observed, from <1% in 2008 to >9% in 2014. Occasionally, outbreaks with linezolid-resistant VRE (ST117) were observed. In total, 232 (92.4%) of 251 linezolid-resistant E. faecium isolates (including 61 vanA and 29 vanB ) contained the G2576T 23S rDNA mutation and showed a varying mixture of wild-type and mutated alleles per genome sufficient to confer linezolid resistance. In vitro growth experiments revealed a stable linezolid MIC. Of the 251 linezolid-resistant isolates, 5 were cfr -positive. In conclusion, these NRC data identified a country-wide ongoing trend of increasing linezolid resistance among clinical E. faecium isolates within the last 5 years.